OPPORTUNITIES FOR THE IMPLEMENTATION OF ACEH CRIMINAL LAW AS NATIONAL LAW FROM THE PERSPECTIVE OF ARTICLE 29 OF THE 1945 CONSTITUTION - Lalu Syaifudin; Gunawan Widjaja; Cecep Suhardiman (ADISAM Publisher, 2025)
This study examines the possibility of recognising Acehnese criminal law as national law in Indonesia, a country known as a constitutional state according to Article 29 of the 1945 Constitution. Through the constitutional guarantee of freedom of religion, this study examines the prospects for the national application of Islamic criminal law in Aceh. The lack of understanding among some members of the public regarding Islamic criminal law has led to the perception that these rules are harsh and inhumane. For example, sharp criticism of the punishment of amputation of the hand in Islamic Sharia often fails to consider the specific conditions that must be met before such a punishment is imposed. The application of Islamic criminal law can be effective, especially if its primary objective is to serve as a deterrent. Conversely, the implementation of this law becomes irrelevant if law enforcement is merely seen as a pragmatic tool or a subject of conceptual debate. A strong constitutional foundation and significant opportunities exist to incorporate Aceh's criminal law into national regulations, given that the 1945 Constitution, particularly Article 29, paragraphs 1 and 2, guarantees freedom of religion.